DEVELOPMENT MODEL APPROACH THROUGH EXERCISE KINESTHETIC GAME CIRCUIT FOR CHILDREN AGES 4-6 YEARS - Bangkit Seandi Taroreh (Program Pascasarjana Universitas Negeri Jakarta, 2017)
AbstractThis study aims to develop a basic kinesthetic based motion activity model for children aged 4-6 years. The design of this study refers to the Borg and Gall development model consisting of ten steps. These steps are 1) preliminary study aims to know the needs analysis in developing physical activity. It was concluded that a basic kinesthetic based motion activity model is required for children aged 4-6 years, 2) planning by formulating forms of participation in research); 3) design development, done by drafting and validated to 4 (four) experts and 1 (one) practitioner with 52 basic motion based kinesthetic activities, 4) conducting limited field test using 20 subjects, 5) revision of field test result limited clarity of implementation procedure and handbook, 6) broader field test using 50 subjects, 7) the revision of the field test results is broader, nothing needs to be revised because all aspects already meet the standards, 8) the main test through the model effectiveness test done 40 subjects, 9) the final product, 10) dissemination. Subjects in this study were children aged 4-6 years in Kindergarten. Place of research conducted in Tangerang City. Data were collected through documentation, observation, questionnaires and kinesthetic tests. Data analysis is done descriptively from qualitative and quantitative data. The results of the study are the basic kinesthetic based motion activity activity for children aged 4-6 years. The results prove that the development of a kinesthetic based motion activity model for children aged 4-6 years has been declared valid by motor learning experts, physical activity experts and early childhood education practitioners.Keywords: basic motion activity, kinesthetic, children aged 4-6 years.